Peritoneal Inclusion Cyst in a pre-pubertal male - Mehran Hiradfar; Reza Shojaeian; Nona Zabolinejad; Reza Nazarzadeh; Ali Azadmand (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2016)
Introduction Peritoneal inclusion cyst (PIC) is a cyst lined with mesothelium and usually full of fluids in the pelvis and it is most usually seen in young women and rarely, they may occur in males. Case Presentation A 12 year old boy was referred with a two-day history of abdominal pain. Abdominal examination revealed lower abdominal tenderness. Laboratory tests were normal. Imaging by abdominal ultrasound and CT scan showed collection of fluid in the pelvis with some septations and lymphadenopathies. Shapeless cystic mass with thin membrane which was independent of abdominal organs was found during laparoscopy and extracted from pelvic cavity. Histopathologic examination established the diagnosis of peritoneal inclusion cyst. Conclusion peritoneal inclusion cyst should be in mind as differential diagnosis in a patient with intra-abdominal cystic fluid collection even in childhood and male gender.